The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1970
DOI: 10.1111/j.1600-0722.1970.tb02098.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Charters‘, scrub and roll methods of toothbrushing by professionals in removing plaque

Abstract: The effectiveness of the Charters', scrub, and roll methods of toothbrushing by professional dental personnel in removing plaque was studied in 60 United States Army recruits. A n interaction between method of brushing and brusher was found, indicating that no one method was clearly most effective in removing plaque. One brusher removed significantly more plaque with the Charfers' method than with the roll method, whereas the other brusher obtained a significantly greater reduction in plaque with the scrub met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…It was also shown that plaque can be removed from at least 1 mm subgingivally. Similar studies (33) of the roll, horizontal scrub and Charters’ techniques all had limited effect on the approximal tooth surfaces, although the Charters’ technique did at least attempt to address the presence of proximal plaque because the method involves holding the head of the brush so that the filaments are at 45° to the tooth surface and pointing in an occlusal direction, whilst using a gentle vibratory motion.…”
Section: Dental Plaquementioning
confidence: 98%
“…It was also shown that plaque can be removed from at least 1 mm subgingivally. Similar studies (33) of the roll, horizontal scrub and Charters’ techniques all had limited effect on the approximal tooth surfaces, although the Charters’ technique did at least attempt to address the presence of proximal plaque because the method involves holding the head of the brush so that the filaments are at 45° to the tooth surface and pointing in an occlusal direction, whilst using a gentle vibratory motion.…”
Section: Dental Plaquementioning
confidence: 98%
“…The original studies conducted were typically short-term, neither did they evaluate gingival health nor demonstrate one method as being consistently superior. [47] The Bass technique[8] was first described in 1954. In the past decade, it has become the method most frequently recommended method as it is easy to learn and emphasizes sulcular placement of bristles.…”
Section: Introductionmentioning
confidence: 99%
“…From clinical studies testing the cleaning efficiency of different toothbrushes where the same brushing method was used (1,2) or testing different brushing methods where the same type of toothbrush was used (3)(4)(5)(6)(7)(8)(9)(10), no significant conclusions can be drawn as to which toothbrush or method was superior to others.…”
mentioning
confidence: 99%